Leiomyosarcoma of the breast: сlinical observations - A. S. Belokhvostova; Yu. A. Ragulin; I. A. Zharikova; V. Ye. Ivanov (Опухоли женской репродуктивной системы)
The paper describes 2 cases of primary or metastatic leiomyosarcoma of the breast. The patient with primary leiomyosarcoma underwent surgical treatment as radical mastectomy in 2011; two years later, there was disease progression with metastases to the lung, bone, stomach; the performed treatment was ineffective; the patient died from disease progression. In the other patient, the breast became one of the metasta- sis-involved organs during process generalization. This pathology is rare and little studied and presented as clinical cases in the literature.